Nguyễn Thu Thảo. Tính hội nhập trong một số từ ngữ quan trọng ngành thông tin-thư viện qua Google - Nguyễn, Thu Thảo (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Utilizes Google as tool to calculate use frequency of some important LIS terms; considers the agreeing degree of thought on the basis of the similarity of terms